Amyloid Dysmetabolism Relates to Reduced Glucose Uptake in White Matter Hyperintensities - Kalheim, Lisa Flem; Selnes, Per; Bjørnerud, Atle; Coello, Christopher; Vegge, Kjetil; Fladby, Tormod (Frontiers in Neurology, 2016)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disorder and cause of dementia, and is characterized by amyloid plaques and neurofibrillary tangles. AD has traditionally been considered to primarily affect grey matter, but multiple lines of evidence also indicate white matter (WM) pathology and associated small-vessel cerebrovascular disease (CVD). WM glucose delivery and metabolism may have implications for local tissue integrity, and [18F]-fluorodeoxyglucose positron emission tomography (FDG-PET) may be helpful to assess neuroglial and axonal function in WM. Hypothesizing that affection of oligodendroglia will be associated with loss of glucose uptake, we aimed to investigate glucose metabolism in MRI white matter hyperintensities (WMHs) and normal-appearing white matter in patients with and without evidence of amyloid plaques. Subjects with mild cognitive impairment or subjective cognitive decline were included and dichotomized according to pathological (Aβ+) or normal (Aβ-) concentrations of cerebrospinal fluid amyloid-β 1-42. A total of fifty subjects were included, of whom thirty subjects were classified as Aβ(+) and twenty subjects as Aβ(-). All subjects were assessed with MRI and FDG-PET. FDG-PET images were corrected for effects of partial voluming and normalized to cerebellar WM, before determining WMH FDG uptake. Although there were no significant differences between the groups in terms of age, WMH volume, number of individual WMHs or WMH distribution, we found significantly lower (p = 0.021) FDG uptake in WMHs in Aβ(+) subjects (mean = 0,662, SD = 0.113) compared to Aβ(-) subjects (mean = 0.596, SD = 0.073). There were no significant group differences in the FDG uptake in normal-appearing white matter. Similar results were obtained without correction for effects of partial voluming. Our findings add to the evidence for a link between Aβ dysmetabolism and white matter pathology in AD.